Dilema Faktor Kepribadian dan Bias Kognitif dalam Perilaku Keputusan Investasi Gen Z - Aprayuda, Riyadi; Prameswari, Saskia Adellia (Akuntansi & Ekonomika, 2026)
This study investigates how personality traits (trait anger, trait anxiety, self-monitoring) and cognitive biases (overconfidence, herding behavior) affect Generation Z investment decision. A quantitative approach was used, with an online survey, from 209 active investors in Investment Gallery of Politeknik Negeri Batam. The analysis results indicate that only overconfidence and herding behavior significantly influence Generation Z’s investment decision, while trait anger, trait anxiety, and self-monitoring show no significant effect. This finding confirms that cognitive biases have a more dominant influence than personality traits in investment decision-making. Overconfidence and herding behavior are the main factors in the investment decisions of Generation Z. This study emphasizes the importance of financial education that builds awareness of psychological biases and provides implications for policymakers in designing education strategies that are appropriate for the characteristics of young investors.